Long Term Safety of Infliximab - Thomas F Schaible (Canadian Journal of Gastroenterology)
Infliximab is a chimeric anti-tumour necrosis factor-alpha monoclonal antibody that has been studied for the treatment of Crohn’s disease and rheumatoid arthritis. In several placebo controlled, randomized clinical trials and open trials, 771 patients have been given infliximab (a further 192 received placebo). Follow-up for safety has included the time of study (12 weeks after the last infusion), plus three additional years. Acute infusion reactions (headache, fever, chills, urticaria, chest pain) were seen in17% of patients receiving infliximab compared with 7% of those receiving placebo. While infections were reported more frequently overall in the patients given infliximab (26% over 27 weeks of follow-up versus 16% of placebo-treated patients over 20 weeks of follow-up), there was no increased risk of serious infections. There was no difference in the overall mortality rate between the groups. While low titres of autoantibodies developed in less than 10% of patients, drug-induced lupus was seen in less than 1%, with these cases resolving upon discontinuation of the drug. Overall, infliximab showed an acceptable safety profile.